Hematological dynamics following the co-administration of Resveratrol and Cisplatin in Sprague-Dawley rats. - Izuchukwu Azuka Okafor; Johnson Okwudili Nweke; Uchenna Somtochukwu Nnamah (National Scientific Medical Center, 2018)
Background: Cisplatin, a platinum-based chemotherapy  agent, is used  in  the  effective treatment  of  a  wide  range  of  malignant cancers. Resveratrol, a polyphenolic plant-derived compound, has been shown to have several biological effects including protecting the body against several forms of damages. Objective: This study assessed the effects of cisplatin and supplementation with resveratrol on some hematological parameters in Sprague-Dawley rats. Material and Methods: Forty-five adult female Sprague-Dawley rats, grouped into 9, were used for this experimental study. Group 1 served as the control group and received distilled water only. Groups 2 and 9 received Cisplatin only while groups 3, 4, and 5 received different doses of Resveratrol after a single dose of Cisplatin. Groups 6, 7, and 8 received Resveratrol before Cisplatin. Results: At the end of administration, blood samples were collected and different hematological parameters were accessed. Groups 2 and 5 showed a significantly higher Total WBC when compared to the control group (p<0.05). Group 7 showed a significantly higher (p<0.05) neutrophil count compared to both the control group and group 2, but a significant decrease in the lymphocyte count compared to the same groups (p<0.05). Groups 6 and 7 showed a significant reduction in monocyte when compared to the control group (p<0.05). There was no significant difference in the eosinophil count of all treatment groups when compared to the control group and cisplatin groups (p<0.05). Basophil increased significantly in group 7 when compared to the control group and group 2 (p<0.05). More so, a significant decrease in the Haemoglobin (Hb), Packed cell volume (PCV) and Mean corpuscular volume (MCV) level were observed when compared to group 9 (p<0.05). Conclusion: This study showed that cisplatin-induced alteration in some hematological parameters is reversible by treatment with resveratrol. More so, resveratrol supplementation should be incorporated as part of dietary nutrients for patients on cisplatin during chemotherapy.